The Antimicrobial Peptide Lysozyme Is Induced after Multiple Trauma. (31st August 2014) - Klüter, Tim; Fitschen-Oestern, Stefanie; Lippross, Sebastian; Weuster, Matthias; Mentlein, Rolf; Steubesand, Nadine; Neunaber, Claudia; Hildebrand, Frank; Pufe, Thomas; Tohidnezhad, Mersedeh; Beyer, Andreas; Seekamp, Andreas; et al.
Abstract : The antimicrobial peptide lysozyme is an important factor of innate immunity and exerts high potential of antibacterial activity. In the present study we evaluated the lysozyme expression in serum of multiple injured patients and subsequently analyzed their possible sources and signaling pathways. Expression of lysozyme was examined in blood samples of multiple trauma patients from the day of trauma until 14 days after trauma by ELISA. To investigate major sources of lysozyme, its expression and regulation in serum samples, different blood cells, and tissue samples were analysed by ELISA and real-time PCR. Neutrophils and hepatocytes were stimulated with cytokines and supernatant of Staphylococcus aureus . The present study demonstrates the induction and release of lysozyme in serum of multiple injured patients. The highest lysozyme expression of all tested cells and tissues was detected in neutrophils. Stimulation with trauma-related factors such as interleukin-6 and S. aureus induced lysozyme expression. Liver tissue samples of patients without trauma show little lysozyme expression compared to neutrophils. After stimulation with bacterial fragments, lysozyme expression of hepatocytes is upregulated significantly. Toll-like receptor 2, a classic receptor of Gram-positive bacterial protein, was detected as a possible target for lysozyme induction.